Study postharvest characteristics, chemical composition and antimicrobial activity of Dianthus caryophyllus L., cut flowers using some essential oils - Soliman, Dina Mahmoud; El-Sayed, Iman Mohamed (Ornamental Horticulture, 2023)
Carnation (Dianthus caryophyllus ‘Servantes’) is a popular and economically cut flower widely used in the florist industry. However, post-harvest senescence occurs in a few days and limits the cut carnation flowers’ commercialization. Therefore, this research was performed to investigate the impact of essential oils such as tea tree oil (TTO), pumpkin seed oil (PSO), Moringa seed essential oils (MEO), and Eucalyptus oils (EEO), as eco-friendly preservative solutions to enhance the quality and longevity of carnation flowers. Carnation cut flowers were submitted to different concentrations (250 and 500 mg L-1) of each essential oil used in the vase solution and the experiments were carried out as a completely randomized design in three replicates. The findings revealed that the longest vase life and the maximum total water solution uptake in cut carnation were achieved when treated with either TTO or PSO oil at 500 mg L-1 in solution preservative as compared to the control (distilled water). While the highest relative fresh weight was observed at 500 mg L-1 PSO, the highest chlorophyll a, b, total carotenoids, total sugar, total phenolic content in leaves, anthocyanin content, and enzyme activity in petals at 500 mg L-1 TTO and PSO. Additionally, all treatments of selected oils have positively declined the bacteria activity compared to control. Also, the lowest bacteria growth on third day with 500 mg L-1 TTO and PSO. However, observing a prim state of xylem vessels with TTO 500 mg L-1and PSO 500 mg L-1, comparable with distilled water, the application of essential oil in this study as a natural preservative in preservative solution as an alternative to chemicals could be of environmental value and great economic.